MANAJEMEN PEMBELAJARAN HAFALAN AL-QUR’AN DI MI AL-BAROKAH PURWANTORO - Siti Rohmatul Imani; Nuraini Nuraini; Anip Dwi Saputro (TARBAWI:Journal on Islamic Education, 2019)
The management of memorization the Qur'an at MI Al-Barokah Purwantoro is an activity carried out by a teacher. Before carrying out learning, the teacher prepares targets or determines memorization first. Al-Qur'an memorization management at MI Al-Barokah purwantoro includes planning and implementation of learning. This research was conducted with the aim to find out the Management of Quran Recitation Learning carried out by each teacher when it will teach memorization of the Qur'an and how the inhibiting factors and supporters. This study uses descriptive qualitative research methods and the data collection is done by interview, observation, and documentation. The results of this study can be concluded that the Management of Al-Qur'an Memorizing Learning at MI Al-Barokah Purwantoro is an activity carried out by the teacher by using targets or determining memorization of the Qur'an. The learning stage 1. Learning planning which includes: a. extracurricular program, b. rote determination. 2. Implementation of learning which includes: a. learning method, b. deposit system, c. memorization target, d. evaluation. In MI Al-Barokah Purwantoro determining the target of the hafala is one juz, namely juz 'amma, and the memorization process of the Koran by using several methods namely by writing method and also by repetition method, by reading verses then students imitating until memorizing then after memorizing then students are required to deposit the memorization.